The morphokinetic signature of human blastocysts with mosaicism and the clinical outcomes following transfer of embryos with low-level mosaicism - Yaoyu Zou; Yilun Sui; Jing Fu; Naidong Ge; Xiaoxi Sun; Yijuan Sun (BMC, 2024)
Abstract Background Genetic mosaicism is commonly observed in human blastocysts. Embryos' morphokinetic feature observed from time-lapse monitoring (TLM) is helpful to predict the embryos' ploidy status in a non-invasive way. However, morphokinetic research on mosaic embryos is extremely limited. Moreover, transfer of mosaic embryos is a new attempt in reproductive medicine, while studies regarding the clinical and neonatal outcomes following transfer of embryos with different levels and types of mosaicism are needed. This study aimed to investigate the morphokinetic characteristics of mosaic blastocysts, uncover clinical outcomes of mosaic embryos, and evaluate the effect of level and type of mosaicism on transfer outcomes. Results A total of 923 blastocysts from 229 preimplantation genetic testing cycles were cultured in TLM incubators in a single fertilization center between July 2016 and July 2021. Multivariate logistic regression models showed mosaic embryos had significantly shorter time to reach morula when compared with euploid (P = 0.002), mosaic with aneuploid (P = 0.005), and aneuploid (P = 0.005) embryos after adjusting the potential confounders. KIDScore is an artificial intelligence scoring program from time lapse incubation system to predict embryo implantation potential. Mosaic with aneuploid embryos had significantly lower KIDScore than euploid (P = 6.47e−4), mosaic (P = 0.005), and aneuploid (P = 0.004) embryos after adjustment. Meanwhile, we compared the clinical outcomes following transfer of low-level (< 50%) mosaic embryos (N = 60) with euploid embryos (N = 1301) matched using propensity scoring collected from September 2020 to January 2023. Mosaic embryos had significantly lower clinical pregnancy rate (41.67% vs. 57.65%, P = 0.015) and live birth rate (38.33% vs. 51.35%, P = 0.048) than the euploid embryos. Subgroup analyses showed the whole, segmental, and complex chromosome mosaic embryos had the similar clinical outcomes. Conclusions The shortened time to reach morula in mosaic embryos and the low KIDScore in mosaic with aneuploid embryos revealed innovative clues to embryo selection with the non-invasive TLM and provided new insights into biological mechanism of chromosomal abnormality. The analyses of overall and subgroups of mosaic embryo transfer outcomes helped to optimize embryo transfer scheme for in-vitro fertilization procedures. Multi-center prospective studies with large sample sizes are warranted to validate our results in the future.